Protection Of Sequence and Communication Technology Equipment Using Smart Grid Application - Archenaa J; E. A. Mary Anitha (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper investigates the merger of energy utility circuits with that of the data and correspondence innovation (ICT) gear under the keen matrix and the security suggestions that this postures, and figures out what is the most extreme voltage that ICT hardware, composed as per IEC 62368-1 can specifically get to control framework circuits. The coming of the keen lattice, the modernization of the power framework utilizing current data and correspondence innovation methods, alongside the expansion of electric vehicle frameworks to the matrix, guarantees to change the business in uncommon manners. In this paper will be utilized as a part of this paper for deciding the level of security of ICT gear must be built to keeping in mind the end goal to be conveyed in higher-voltage application.